Models for delivering high quality emergency neurosurgery in high income countries - Boissaud-Cooke, Matthew A. (Cambridge University Press, 2024)
Emergency neurosurgery encompasses serious and high-risk cranial and spinal conditions across all ages. The authors provide an overview of the changes occurring within emergency surgery to meet the challenges provided from unscheduled care. Considering the wider landscape of emergency surgery provides a context for the changes occurring within emergency neurosurgery. The delivery of emergency neurosurgery within the UK, the Republic of Ireland, the Netherlands, and the United States of America (USA) is then described to provide an overview of different models of care
Title from publisher's bibliographic system (viewed on 12 Jan 2024)
Keywords: Nervous system / Surgery